دراسة بعض المواصفات الكيميائية وتحديد السكاريدات بتقانة HPLC لبعض أنواع ثمار الحمضيات (برتقال وليمون) في الساحل السوري (Latakia University Journal -Basic Sciences Series, 2018)
تُعد دراسة مكونات الثمار من المركبات وبصورة خاصة السكاريدات على درجة من الأهمية بسبب ارتباطها المباشر بالحالة الفيزيولوجية للثمرة. دُرست عصائر ثمار الحمضيات برتقال وليمون من أصناف مختلفة لموسم 2000-2001 مصدرها الساحل السوري. تمّ تحديد قرائن مثل النسبة المئوية للعصير وكثافة العصير والنسبة المئوية للماء في العصير والمواد الصلبة الذائبة والنسبة المئوية للحموض الحرة وقيمة pH العصير إضافة لدليل النضج. كما دُرس محتوى عصائر الثمار من السكاريدات الأحادية (الغلوكوز والفركتوز) والثنائية (السكروز) بتقانة الكروماتوغرافيا السائلة عالية الأداء (HPLC) مستخدمين عموداً مطعماً بالزمر الأمينية بمثابة طور ثابت(NH2-Type) ، وأسيتونتريل-ماء كطور متحرك مع مكشاف قرينة الانكسار RID، تميزت هذه الطريقة بتفريق جيد للسكاريدات وسرعة في إنجاز التحليل. من خلال ذلك تمَّ توصيف ثمار البرتقال (أبو صرة، سكري، بلدي، ماوردي، يافاوي، فالنسيا) والليمون (ماير محسن) من المنشأ السوري بإيجاد قيم القرائن المميزة لها بهدف مقارنتها مع مثيلاتها من الأصناف الأجنبية.The study of the components of fruit is very important specially it’s content of saccharides, because of its direct relation with the phyisological state of the fruit. The juice of different kinds of citrus fruit Orange and Improved Mayor from the Syrian coast were studied for the season 2000-2001. Different clues such as the precentage of juice content, moisture, total soluble solids, acidity, pH, maturity index, had all been determined. Also the content of Monosaccharides (Glucose and Fructose) and Disaccharides (Sucrose) in citrus juice had been determined with High-Performance Liquid Chromatography (HPLC) by using a polyamine-bonded polymer gel (NH2- Type) column with acetonitrile-water as mobile phase, in the addition to differential refractometer detector RID. This highly sensitive method was more accurate and rapid for determining saccharide contents in citrus juice. The specifications of citrus juice fruit (Orange: Navel, Succari, Comun Orange, Maourdi, Shamouti, Valencia and Lemon: Improved Mayor) from Syrain origin had been determined by finding its specific qualifications (clues) in order to compare them with similar specifications of foreign kinds.